NUTRITIONAL STATUS OF PREGNANT WOMEN IN RELATION TO THE PREVALENCE OF INFANT LOW BIRTH WEIGHT (LBW) (Case Study in Sugihwaras, Bojonegoro during 2017) - Fajrin, Fitriana Ikhtiarinawati (Journal of Research and Technology, 2018)
Nutritional status is an important thing to consider during pregnancy, as it will significantly affect the development and growth of the fetus. Hence, maternalnutritional factors both before and during pregnancy account for the quality of newborn. Nutritional status of the pregnant women is assessed using mid-upper arm circumference determination, body weighing, and laboratory test. Undernutrition status in pregnant women needs immediate treatment due to the risk and complication for both mother and fetus such as anemia, bleeding, mother's weight does not grow normally, and infectious diseases. Furthermore, it may result in difficult and prolonged labor, preterm delivery, bleeding after delivery, and eventually cesarean delivery tends to increase. While the impact of malnutrition in pregnant women to the fetus that can affect the process of fetal growth and can lead to miscarriage, abortion, stillbirth, neonatal death, congenital defects, anemia, asphyxia intrapartum (dead in the uterus), infant low birth weight (LBW) (Fajrin, 2017). However, there are many pregnant women who have nutritional problems especially undernutrition or known as Chronic Energy Deficiency (CED). The results of the National Socio-Economic Survey (SUSENAS) 1999 showed that there were 27.6% of CED pregnant women is associated with LBW (Lubis, 2003 in Hanifa, 2009). Then, it also can cause premature and immatureLBW (Kusparlina, 2016).MostLBW infants in developing countries are affected by intrauterine growth restriction(IUGR)due to malnutrition, anemia, malaria and sexually transmitted disease (STD) before conception or during pregnancy. It was reported in 2016 that the cases of LBW were 879 infants (4,9%) from a total of 17,041 live births. While there was no significant difference between male and female infants were 429 out of 8,834 and 450 out of 8,207 respectively.Moreover, it was found in Bojonegorothat LBW is the highest cause of infant mortality compared to other causes such as asphyxia, birth trauma, infection, congenital abnormalities and others. Some risk factors that exist in pregnant women who will give birth to babies with LBW are pregnant women with CED, anemia, hypertension, and preeclampsia (DINKESKABBojonegoro, 2016).Infant mortality due to LBWslightly increased from 40%in 2015 to 41.48% in the following year then it is still increasing from year to year (DINKESKABBojonegoro, 2016).To our knowledge, there are no available data of the cause of LBW in Bojonegoro especially in the matter of the nutritional status of the pregnant women. So that the objective of the present study was to determine relationship between the nutritional status of the pregnant women and the prevalence of LBW.